2021
DOI: 10.3233/aiad210013
|View full text |Cite
|
Sign up to set email alerts
|

Particulate Matter Exposure Exacerbates Amyloid-β Plaque Deposition and Gliosis in APP/PS1 Mice

Abstract: Background: Alzheimer’s disease (AD) is a progressive neurodegenerative disorder characterized by the accumulation of amyloid-β (Aβ) plaques, neuroinflammation, and neuronal death. There are several well-established genetic and environmental factors hypothesized to contribute to AD progression including air pollution. However, the molecular mechanisms by which air pollution exacerbates AD are unclear. Objective: This study explored the effects of particulate matter exposure on AD-related brain changes using th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Also, PM 2.5 exposure increases the activity of poly (ADP-ribose) polymerase (PARP)-1, which promotes the formation of amyloid- β , and shows excessive activity of glial cells as evidence of neuroinflammation [ 64 ]. Exposure to PM 2.5 increased the levels of soluble and insoluble amyloid- β and phosphorylated tau protein in mouse brain tissue [ 65 , 66 ]. In this study, EFEL reduced the expression levels of protein related to inflammatory responses in the lung and brain tissues of mice and decreased the expression levels of amyloid- β and p -tau in the brain tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Also, PM 2.5 exposure increases the activity of poly (ADP-ribose) polymerase (PARP)-1, which promotes the formation of amyloid- β , and shows excessive activity of glial cells as evidence of neuroinflammation [ 64 ]. Exposure to PM 2.5 increased the levels of soluble and insoluble amyloid- β and phosphorylated tau protein in mouse brain tissue [ 65 , 66 ]. In this study, EFEL reduced the expression levels of protein related to inflammatory responses in the lung and brain tissues of mice and decreased the expression levels of amyloid- β and p -tau in the brain tissue.…”
Section: Discussionmentioning
confidence: 99%
“…AD is a neurodegenerative (see Glossary) disorder that typically presents in individuals over 65 years old, has a wide variety of symptoms, and is the most common form of dementia [4][5][6][7] (Box 2). Recent studies have found positive correlations between PM exposure and dementia incidence in human cohorts after adjusting for community-and individual-level social and economic characteristics [8][9][10]. Furthermore, mouse models exposed to PM displayed elevated AD biomarkers compared with filtered air (FA) controls [10].…”
Section: Can Particulate Matter Exposure Exacerbate Ad Development?mentioning
confidence: 99%
“…Recent studies have found positive correlations between PM exposure and dementia incidence in human cohorts after adjusting for community-and individual-level social and economic characteristics [8][9][10]. Furthermore, mouse models exposed to PM displayed elevated AD biomarkers compared with filtered air (FA) controls [10]. Studies have also shown PM exacerbates the aggregation and deposition of the AD hallmarks amyloid beta plaques (Aβ) and neurofibrillary tangles (NFTs) in the brain through mechanisms related to microglia/astrocyte activation, oxidative stress, immune activation, and neuroinflammation [3,[10][11][12][13].…”
Section: Can Particulate Matter Exposure Exacerbate Ad Development?mentioning
confidence: 99%
See 1 more Smart Citation